Titanium Dioxide (TiO2) Doped Reduced Graphene Oxide (rGO) with Different Dye for Solar Cell Application - Siti Kudnie, Sahari; Afiqah, Bahrin; Rafidah, Kemat; Muhammad, Kashif; Nur Tahirah, Razali; Zainab, Ngaini; Mohamad Rusof, Mahmood; Uda, Hashim; Marini, Sawawi; Kuryati, Kipli; Rohana, Sapawi; Nazreen, Junaidi (Trans Tech Publications Ltd., 2020)
In the present work, the surface morphology and electrical characteristic of different doping ratio of reduced Graphene Oxide (rGO) in Titanium Oxide solution with different organic dyes (turmeric and beetroot) were studied. The Titanium Dioxide (TiO 2 ) solution and reduced Graphene Oxides (rGO) were synthesized by using precipitation-peptization method and chemical reagent, respectively. The TiO 2 -rGO thin film was deposited on the glass substrate by using doctor-blade technique. The surface morphology and electrical characteristic were measured by using Scanning Electron Microscope (SEM) and Keitheley 2450 Source Meter, respectively. Experimental results showed that 0.3 wt% rGO with turmeric dye resulted the highest value of open voltage (V oc ) and short circuit current (I sc ) of Dye-sensitized Solar Cells (DSSC).